KEMARAHAN JOKO WIDODO DALAM PEMBINGKAIAN MEDIA DARING - Ariyan Alfraita; Fitria Widiyani Roosinda; Delmarrich Bilga Ayu Permatasari (LPPM Stikosa - AWS, 2021)
ABSTRACT The video showing the anger of President Joko Widodo during a plenary session at the State Palace invited various comments from several parties. This incident also did not escape the media coverage. This study analyzes the news about President Joko Widodo's anger. The identification of the news was taken from three online media, namely Kompas.com, JawaPos.com and Tempo.co, using four dimensions of Robert Entman's model framing analysis, namely: Define the problem, Diagnose cause, Make moral judgment and Treatment recommendation. The approach in this research is qualitative. The results of this study indicate that the three online media above have their respective points of view in reporting President Joko Widodo's anger during the plenary session. Keywords: framing analysis; Entman; online media; president's anger